1993
DOI: 10.1017/s0305000900008370
|View full text |Cite
|
Sign up to set email alerts
|

Joint picture-book reading correlates of early oral language skill

Abstract: The purpose of this study was to explore the relation between joint picture-book-reading experiences provided in the home and children's early oral language skills. Subjects were 41 two-year-old children and their mothers. Measures included maternal report of the age at which she began to read to the child, the frequency of home reading sessions, the number of stories read per week, and the frequency of visits by the child to the local library. Measures of language skill used were the child's receptive and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
166
1
16

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(193 citation statements)
references
References 17 publications
(14 reference statements)
10
166
1
16
Order By: Relevance
“…In her study, DeBaryshe (1993) found that the age at which 41 two-year-old children were first read to was a better predictor of oral language skills than the frequency with which children were read to or visited the library. It should be noted that correlational data only were used and no control variables for family or child characteristics were included in this analysis.…”
Section: Hle and Reading To Childrenmentioning
confidence: 95%
See 1 more Smart Citation
“…In her study, DeBaryshe (1993) found that the age at which 41 two-year-old children were first read to was a better predictor of oral language skills than the frequency with which children were read to or visited the library. It should be noted that correlational data only were used and no control variables for family or child characteristics were included in this analysis.…”
Section: Hle and Reading To Childrenmentioning
confidence: 95%
“…However, despite a few studies analyzing the onset of reading (e.g., DeBaryshe, 1993;Niklas, Cohrssen, Tayler, & Schneider, 2016), there are still questions to answer. This study uses data from an Australian study to analyze the association of the onset of parent-child reading with (a) the frequency with which children were read to in the year prior to commencing formal school education, and (b) various child outcomes.…”
Section: The Current Studymentioning
confidence: 99%
“…Si bien numerosos estudios han puesto de manifiesto el efecto positivo de la lectura repetida (BORZONE, 2005) e incluso de la lectura dialógica (SWINSON, ELLIS, 1988;CRAIN-THORESON, DALE, 1992;DEBARYSHE, 1993;ARNOLD et al, 1994;WASIK, BOND, 2001) en las habilidades narrativas de los niños, en estos trabajos no se ha identificado cuál de las tareas llevadas a cabo durante la reconstrucción del cuento y en qué circunstancias podrían dar cuenta de ese efecto positivo. El presente artículo busca identificar precisamente cuáles son las condiciones en las que la reconstrucción de un cuento puede resultar un contexto favorecedor para el desarrollo de las habilidades narrativas en salas de jardín de infantes, describiendo las operaciones cognitivas y discursivas que promueve cada tipo diferente de reconstrucción de cuentos.…”
Section: El Rol Del Adulto: Cómo Apoyar El Procesounclassified
“…Investigations of the value of books for developing children's language have found an association between the amount of literacy activities in the home, (such as the number of books, trips to the library and shared reading activities) and children's language outcomes at 4 years of age (Payne et al 1994;Debaryshe, 1993). Debaryshe found that, the earlier the age of onset of shared reading activities, the better the language outcomes at two years of age, particularly their receptive language.…”
Section: What Parents Havementioning
confidence: 99%